PENGARUH KECEMASAN MATEMATIKA TERHADAP HASIL BELAJAR MATEMATIKA SISWA PADA MATERI ALJABAR DI SEKOLAH MENENGAH PERTAMA KABUPATEN PESISIR SELATAN - Okviani Syafti; Rahmadhani Rahmadhani; Antoni Rahman; Khaira Nisa; Adevi Murni Adel; Devina Shafira Maharani (STKIP Pesisir Selatan, 2026)
This research aims to analyze the influence of mathematics anxiety on student learning outcomes in algebra material. Mathematics anxiety is one of the psychological aspects that can influence student success in the learning process. This research applies a quantitative approach with an ex-post facto correlational design. The population in this research is all junior high schools in Pesisir Selatan Regency, totaling 80 schools. And as a sample, UPT SMPN 4 Painan was selected by random sampling. Mathematics anxiety data was collected using a questionnaire in the form of a Likert scale, while learning outcome data was obtained through algebra material tests. Data analysis was carried out using descriptive statistics and the Pearson correlation test. The research results show a correlation coefficient value of r = -0.67, which indicates a strong negative relationship between mathematics anxiety and algebra learning outcomes. In addition, the coefficient of determination of 0.45 indicates that mathematics anxiety contributes 45% to variations in student learning outcomes. These findings indicate that an increase in the level of mathematics anxiety tends to be followed by a decrease in the learning outcomes achieved by students. Therefore, efforts are needed from teachers and schools to develop effective learning strategies in reducing mathematics anxiety in order to improve student learning outcomes.